2017
DOI: 10.21608/jpp.2017.41985
|View full text |Cite
|
Sign up to set email alerts
|

An Attempt to Alleviation of Irrigation Water Deficit Stress in Cabbage (Brassica oleracea Var. Capitata L.) by Exogenous Foliar Application with some Antioxidant

Abstract: Two field experiments were carried out during the two winter seasons of 2015 and 2016 under clay loamy soil conditions using surface improving irrigation system at the Experimental Station, Faculty of Agriculture, Mansoura University, Dakahlia governorate, Egypt. to study vegetative growth and yield of cabbage (cv. o.s. cross) influenced by irrigation water deficit treatments in three levels include without stress as control (full irrigation), moderate and severe stresses (75 % and 50 % from the control, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
(16 reference statements)
1
1
0
Order By: Relevance
“…This change in Na + and K + level could be attributed to the ability of chitosan in improving the growth of tomato plants or throughout osmolytes content increases, which acquire a plant balance in facing salinity stress. These results are in harmony with the results of [ 71 , 81 ], who also reported that chitosan treatment significantly increased Na + and K + content in salinity stress wheat plants.…”
Section: Discussionsupporting
confidence: 91%
“…This change in Na + and K + level could be attributed to the ability of chitosan in improving the growth of tomato plants or throughout osmolytes content increases, which acquire a plant balance in facing salinity stress. These results are in harmony with the results of [ 71 , 81 ], who also reported that chitosan treatment significantly increased Na + and K + content in salinity stress wheat plants.…”
Section: Discussionsupporting
confidence: 91%
“…It has antioxidant functions, dissolves in water and has an important protection role against reactive oxygen species that consisted during the photosynthesis and respiration (2,19). Metwaly (33) noted that the foliar application of ascorbic acid on the cabbage plant had a significant increment on plant height, leaves area, chlorophyll content, yield, and vitamin C concentration. It was also found (36) that the foliar application of ascorbic acid on broccoli plant for both seasons had a significant increment on leaves area, yield, and the concentration of vitamin C. Balouchi (13) noted that immersion of the flowering heads in the ascorbic acid was significantly increased the shelf life, the concentration of vitamin C, chlorophyll content, TSS, and recorded the least weight loss, these results agreed with (15), It was also found (6) Ascorbic acid significantly increased all vegetative growth, physical and chemical fruits properties of olive.…”
Section: Introductionmentioning
confidence: 99%